2007
DOI: 10.1021/cm0717357
|View full text |Cite
|
Sign up to set email alerts
|

Norbornene-Based Copolymers with Iridium Complexes and Bis(carbazolyl)fluorene Groups in Their Side-Chains and Their Use in Light-Emitting Diodes

Abstract: Solution-processable copolymers with pendant phosphorescent iridium complexes and 2,7-di(carbazol-9-yl)fluorene-type host moieties were synthesized using ruthenium-catalyzed ring-opening metathesis polymerization. Low polydispersity indices and molecular weights around 20 000 Da were obtained for all copolymers. As a result of the living character of the polymerization of the monomer containing the host moiety, a high degree of control over the molecular weights of all copolymers can be obtained. The photo-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…Weck and co-workers used the ring-opening metathesis polymerization (ROMP) of functionalized exo-norbornene [134,136] or cyclooctene monomers [135] to synthesize homo-and copolymers equipped with Ir III emitters. A first proof of the feasibility was gained by polymerizing norbornenes bearing tris-cyclometallated (facial and meridional) complexes as well as charged bis-cyclometallated iridium(III) bipyridine complexes and by performing copolymerizations with alkyl-functionalized norbornene.…”
Section: Complex-containing Polymers: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weck and co-workers used the ring-opening metathesis polymerization (ROMP) of functionalized exo-norbornene [134,136] or cyclooctene monomers [135] to synthesize homo-and copolymers equipped with Ir III emitters. A first proof of the feasibility was gained by polymerizing norbornenes bearing tris-cyclometallated (facial and meridional) complexes as well as charged bis-cyclometallated iridium(III) bipyridine complexes and by performing copolymerizations with alkyl-functionalized norbornene.…”
Section: Complex-containing Polymers: Synthesis and Propertiesmentioning
confidence: 99%
“…[135] Further on, norbornenes bearing various heteroleptic tris-cyclometallated Ir III complexes were copolymerized with a (bis-carbazole-fluorene)-norbornene derivative. [136,137] Testing several materials in a multilayer device assembly, a maximum efficiency of 4.9% (at 100 cd m 2 ) could be realized. [137] Ulbricht and co-workers [138] and Rehmann et al [139] reported the synthesis of oxetane-functionalized bis-cyclometallated iridium(III) acetoacetate complexes and the optimization of multilayer OLEDs employing these emitters, which were covalently incorporated into a crosslinked matrix.…”
Section: Complex-containing Polymers: Synthesis and Propertiesmentioning
confidence: 99%
“…According to the Equations shown in Figure 3, [19][20][21]23,24,[28][29][30] has received some attention in polymeric side chains. [31][32][33] Despite the limited binding constant data available for the environments in which supramolecular polymer chemistry studies have been conducted, a variety of interesting materials have been reported. The focus below shifts from fundamental binding constant studies to a discussion of synthetic methods used to generate macromolecules inspired by Figure 1 and then a brief highlight of various materials generated from these novel macromolecules.…”
Section: Terpyridine-metal Binding Constantsmentioning
confidence: 99%
“…[25] More recently the electroluminescence of poly(norbornene) based devices was reported. [39,40] With several recent reviews available, [6,41] and the fact that a detailed review of this area is well beyond the scope of this Feature Article, further discussion on these important transition metal-containing polymers will be deferred so that attention can be given to lanthanide-based materials.…”
Section: Highly Emissive Transition Metal-containing Polymersmentioning
confidence: 99%